Vermicompost and NPSZnB Fertilizer Levels on Maize (Zea mays L.) Growth, Yield Component, and Yield at Guto Gida, Western Ethiopia - Abdela Tufa (International Journal of Agronomy)
The application of organic and inorganic fertilizers together increases crop productivity and soil fertility. However, it is crucial to identify the combined application level. A field experiment was carried out in the Guto Gida district in 2021 to determine the effect of vermicompost levels and chemically mixed NPSZnB fertilizer rates on the growth and yield of maize. Four vermicompost levels (0, 2.5, 5, and 7.5 t·ha−1) combined with four artificial NPSZnB fertilizer rates (0, 50, 100, and 150 kg·ha−1) were used for the study in a randomized complete block design (RCBD) with 3 replicates. Crop phenology and biomass yield were both significantly influenced by the main effects of vermicompost level and NPSZnB rate. Vermicompost and NPSZnB fertilizer applied together had a large effect on plant height, leaf area index, ear weight, thousand kernel weight, and grain yield. The largest grain yield (8.03 t·ha−1) was produced by the interaction of vermicompost at 7.5 t·ha−1 with 150 kg·ha−1 NPSZnB, followed by all levels of vermicompost at and above 5 t·ha−1 with 100 and 150 kg·ha−1 NPSZnB. Additionally, plots treated with a combined application of vermicompost and NPSZnB fertilizer at rates of 5 t·ha−1 × 100 kg·ha−1 and 5 t·ha−1 × 150 kg·ha−1, respectively, recorded the greatest values of ear weight (276.1 g) and thousand kernel weight (49.79 g). However, the lower yield was obtained from plots that were untreated with both vermicompost and NPSZnB, and the plot treated only with 50–150 kg·ha−1 of NPSZnB. In conclusion, integrated applications of vermicompost at 5 t·ha−1 and NPSZnB fertilizer at 100 kg·ha−1 increased maize yield by about 10.36%, with a net benefit of 140486.00 ETB·ha−1 and a marginal rate of return of 797.98%. As a result, vermicompost application at 5 t·ha−1 rate with synthetic NPSZnB fertilizer at 100 kg·ha−1 is found suitable for the study area.